Old lead, new challenges: Is there a safe level of exposure? - Javorac, Dragana; Marić, Djurdjica; Baralić, Katarina; Andjelković, Milena; Antonijević Miljaković, Evica; Buha Djordjević, Aleksandra; Djukić-Ćosić, Danijela; Ćurčić, Marijana; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2022)
Lead (Pb) is one of the most important toxic metals without known physiological role. Recent data indicate that any exposure, even low, can be harmful. Therefore, safe blood lead levels, as well as tolerating daily intake, have not been identified. In adults, the most sensitive effect is increase in systolic blood pressure, while in children, the most sensitive effect is on cognition. Therefore, the aim of this study was to examine the effects of low lead doses on the central nervous and cardiovascular system in a rat model. The study was conducted on Wistar rats (n = 42; 7 groups) treated for 28 days, with increasing doses of 0.1; 0.5; 1; 3; 7; 15 mgPb/kg b.w./day to simulate real exposure. After the sacrifice, the brain and heart were isolated, in which the parameters of oxidative status, bioelements and lead levels were determined. Benchmark modelling of the dose-effect relationship was performed using PROAST 70.1 software (RIVM, Netherlands). The obtained results indicate that lead leads to the induction of oxidative stress and dishomeostasis of bioelements. The lowest value of the Benchmark dose (BMD) was obtained for increase the total oxidative status in the brain (4.49e-06 mgPb/kg/b.w./day), which is the most sensitive effect. In the case of heart, the most sensitive effect was increase in malondialdehyde (BMD: 0.000248 mgPb/kg/b.w./day). Obtained results indicate that low lead doses have toxic effects on heart and brain. Obtained BMD may be useful in assessing human health risk of low lead dose exposure.